Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

Travail-famille : un défi pour les femmes à Cotonou - Adjamagbo, Agnès; Gastineau, Bénédicte; Kpadonou, Norbert (Recherches Feministes, 2016)
En Afrique de l’Ouest, le taux d’activité des femmes est élevé. Souvent cantonnées dans le secteur informel, elles contribuent pourtant de façon importante aux revenus du ménage. Toutefois, les rôles socialement prescrits imposent aux femmes la quasi-intégralité des tâches domestiques et des soins aux enfants. Cet article étudie la manière dont les femmes actives à Cotonou, au Bénin, gèrent leur quotidien entre contraintes familiales et obligations professionnelles. L’analyse montre que la conciliation incombe à toutes les femmes, quel que soit leur milieu socioéconomique. La différence se joue plutôt dans les ressources sociales et financières dont elles disposent pour pallier le fardeau de la double journée.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; approches et analyses; bénin; charge mentale; conciliation famille-travail; discipline; division sexuelle du travail; double journée de travail; démographie; famille; inégalités; maternité; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; systèmes d'oppressions; thématiques; travail; travail domestique

Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation

Égalité femmes-hommes en Afrique de l'Ouest (Secrétariat du Club du Sahel et de l'Afrique de l'Ouest)
En Afrique de l’Ouest, de grandes inégalités entre les sexes persistent. Les femmes et les filles sont défavorisées dans de nombreux domaines et n’ont pas les mêmes opportunités que leurs homologues masculins. Le Secrétariat du CSAO a compilé les documents relatifs aux politiques et stratégies en matière de genre pour faciliter l’accès aux politiques et cadres institutionnels existants et leur diffusion.
Keywords: 2000 à aujourd'hui; 2010-2019; OFDIG; afrique; approches et analyses; inégalités; politique; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; égalité des sexes; égalité femme*-homme